2019
DOI: 10.1177/2324709619844289
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Radial Nerve Palsy as a Complication After Anterior Dislocation of the Glenohumeral Joint: A Case Report and Clinical Review

Abstract: Shoulder dislocation is the most common feature in emergencies, while the anterior dislocation of the glenohumeral joint is the most frequent and requires reduction. Accompanied nerve injury is common with an incidence of 21%, while radial nerve palsy is very rare. We describe the case of a 56-year-old man who presented with an anterior dislocation of the left shoulder due to a fall on an outstretched hand with wrist drop 8 hours after injury. Neurological examination revealed loss of sensation along the radia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Distal radius fractures constitute a common orthopaedic trauma met in emergency department and a remarkable social problem. Most patients with DRF trauma seeking medical help in emergency department need surgical treatment if meeting certain criteria as displaced distal radius fracture with an intra-articular step of more than 2mm, radial shortening more than 2mm, dorsal tilt more than15 degree, incongruence in distal radio-ulnar joint in preoperative x-rays or ct/scan and bilateral DRF [2] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Distal radius fractures constitute a common orthopaedic trauma met in emergency department and a remarkable social problem. Most patients with DRF trauma seeking medical help in emergency department need surgical treatment if meeting certain criteria as displaced distal radius fracture with an intra-articular step of more than 2mm, radial shortening more than 2mm, dorsal tilt more than15 degree, incongruence in distal radio-ulnar joint in preoperative x-rays or ct/scan and bilateral DRF [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Distal radius fracture (DRF) is the most common injury in emergency department with an incidence of 36.8/10 persons per year in women and 9.0/10 persons per year in men over 35 years old rising in 9% by the age of 90years [1,2] . Huetteman et al suggested that the average cost of care for a distal radius fracture patient was up to eight thousand dollars in the United States during 2009-2015 [1] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Wang et al, 2009) In order to preserve a complete passive range of motion in all joints and then he began physiotherapy for the wrist and ingers. (Kastanis et al, 2019) The ROM of the shoulders ( lexion, extension, abduc-tion, rotation), elbows ( lexion, extension, supination, pro-nation), and wrists ( lexion, extension) was measured with a standard goniometer. (Ekholm et al, 2008) At 4 weeks, mobilization begins.…”
Section: Figure 1: Resisted Lexion and Extension (Manually)mentioning
confidence: 99%